Use of the Kaisa Method in learning Arabic vocabulary at the Bone Qur'an Hafidz Madrasah - Nur Aisyah; Andi Abd. Muis; Ruslan; Muharrir Na'iem; Wisriani; Raden Muliana; Mu'minayah (Universitas Muhammadiyah Palu, 2025)
Education in Arabic uses several terms, namely, al-ta'lim, al-tarbiyah, and al-ta'dib. Al-ta'lim is the delivery of correct knowledge, understanding, comprehension, responsibility and instilling trust in children. The type of research used is descriptive qualitative research. Vocabulary is one of the three elements of language that must be mastered, this vocabulary is used in written and spoken language, and is one of the tools to develop one's Arabic language skills. Method is a way used to convey a plan that has been prepared to achieve learning objectives, while learning itself is a deliberate and planned effort by the educator, so as to enable the creation of a conducive learning atmosphere and activities for students. So from the description above, it can be concluded that the learning method is a systematic way of delivering material to students in order to achieve the desired goals. The use of the Kaisa method is one of the movement methods or known as the kinesthetic method carried out in memorizing the Quran. From the research results, the researcher concluded that the Kaisa method is also a combination of various movements, namely theater, dance, karate or silat movements that are adjusted to facial expressions, so that the Kaisa method is very enjoyable when used in learning Arabic vocabulary, because it is able to attract the attention of students and also provides a relaxed impression to students in memorizing vocabulary through their movements. This method is also very suitable for play-age students.